Characterization and presence of ica genes in coagulase-negative staphylococci isolates in a public hospital in Malaysia - Vnayakam, Subashini (2017)
Coagulase-negative staphylococci (CoNS) are often considered as contaminants or normal skin flora but in the past few decades, they had emerged as pathogenic bacteria causing serious infections especially in patients with prosthetic medical devices. Their ability to produce biofilm on polymer surfaces results in treatment failure as it increases the resistance to antibiotics and host defense. Biofilms formation are mediated by polysaccharide intercellular adhesin (PIA), encoded by intercellular adhesion (ica) genes and it has been postulated that the presence of ica genes in CoNS is associated with antimicrobial resistance and responsible for catheter and medical device-related sepsis. The aim of this study is to determine the species distribution, antibiotic susceptibility pattern and to detect the presence of ica genes (icaA, icaD, icaB, and icaC) among CoNS isolated from blood culture. This cross-sectional study was conducted between January 2015 and December 2015, with CoNS isolates obtained from the blood cultures of patients at Hospital Serdang. Coagulase negative staphylococci were identified by gram staining, catalase and coagulase test, followed by species identification by Analytical Profile Index (API) Staph identification strips. Antimicrobial susceptibility testing was performed using Kirby Bauer method interpreted according to the Clinical and Laboratory Standards Institute guidelines. The presence of ica genes were detected using multiplex polymerase chain reaction. Staphylococcus epidermidis dominated the total number of species isolated (n=64, 40.0%). A total of 160 CoNS, 72.5% were resistant to penicillin and 60% were methicillin-resistant (MR) CoNS. Majority of CoNS harbored icaD (59.3%) and in 4 (2.5%) strains, all icaADBC genes were observed. Detection of ica genes indicates CoNS are able to produce biofilm that causes serious nosocomial infections and should not always be reported as colonizer or contaminants.